Esophageal Stricture Caused by CMV in a Non-HIV-Infected Renal Transplant Patient. Issue 8 (31st August 2022) - Tennant, Tamera C.; Pandey, Samiksha; Edhi, Ahmed I.; Batke, Mihaela
ABSTRACT: Esophageal stricture due to cytomegalovirus (CMV) infection is an uncommon pathology, with most reported cases occurring in patients infected with human immunodeficiency virus. We report a renal transplant patient who presented with progressive dysphagia and weight loss for 2 years. Endoscopic examination revealed a long esophageal stricture with a necrotic lesion but no typical CMV esophageal ulcers; immunostains were positive for CMV. Dysphagia resolved after treatment with ganciclovir and serial esophageal dilations. We are presenting the first case of esophageal stricture due to CMV esophagitis in a renal transplant patient without human immunodeficiency virus infection and are reviewing current literature.